OPTIMALISASI MINAT BACA SISWA SDN 1 TALANG PANGERAN MELALUI PENDEKATAN EMOSIONAL THORIQOH MUHADHOROH - Ihsan, Daniel Nadhif (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2025)
Reading holds great benefits for individuals in acquiring lessons about life. Success in reading is a hope for teachers and parents, as reading is a crucial aspect in the learning process. Muhadhoroh, as an art of storytelling, is considered effective in instilling moral values in listeners, including students, without displaying a preachy attitude. This research aims to enhance students' reading interest at SDN 1 Talang Pangeran through the emotional approach of Thoriqoh Muhadhoroh. The research method employed is qualitative with a descriptive design. The results indicate an increase in students' reading interest after implementing muhadhoroh, although there are still weaknesses that need to be addressed. Improvements made in phase II, such as enhancing learning activities and rewarding students' achievements, have yielded satisfactory results. This is evidenced by more than 50 percent of students achieving good grades at the end of cycle II, indicating that the muhadhoroh activities conducted have been successful in effectively enhancing students' reading interest.